Brahms i Rachmaninow Iwaszkiewicza - Tenczyńska, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The poetry of Jarosław Iwaszkiewicz includes various – and unique in the 20th century Polish literature – references to actual musical compositions. Johannes Brahms and Sergei Rachmaninoff are among the composers, whose pieces are most often present in this poetry. Close reading of chosen poems, which conduct intertextual and intersemiotic dialog with Brahms’ and Rachmaninoff’s compositions, allows one to distinguish various models of this dialog and its functions. It becomes possible – in the wider biographical context – to ask about the meaning of German and Russian music to the writer and to the, often autobiographical, subjects of his poems. It leads also to the question of the relation between music and memory in Iwaszkiewicz’s poetry, based sometimes on a surprising counterpoint with respect to the sérénité motive. In the context of this relation another motive seems to come to the fore, the motive of the lost world, to which, as the protagonist of Brzezina says, ‘I will never return, and which I have never truly experienced’.